FACTORS INFLUENCING THE ORGANIZATIONAL COMMITMENT OF TEACHERS UNDER THE SECONDARY EDUCATIONAL SERVICE AREA OFFICE 3 - ประเสริฐชาติ, สุชาพร; ไชยชมพู, สุรัตน์; ทองแพง, ธนวิน (Academic Journal Phranakhon Rajabhat University, 2018)
The purposes of the study were to study the factors about individual characteristics work characteristics and work experience of the teachers, to study the factors of teachers’ commitment, to study about the relationship between individual characteristics work characteristics and work experience of the teachers, to study the factors that influencing the organizational commitment of teacher, to create an equation that predicts the teacher's organization commitment under The Secondary Educational Service Area Office 3 by using individual characteristics factor, work characteristics factor and work experience factor as predictors by using questionnaire created by the researcher. The sample group of this research was 341 teachers in secondary schools under The Secondary Educational Service Area Office 3. The sample group was determined by using Krejcie & Morgan’s formulaic table. Statistics used in data analysis were basic statistics for calculating percentage, Mean, Standard Deviation, Pearson’s product moment correlation coefficient, and Stepwise Multiple Regression Analysis in order to analyze factors influencing the organizational commitment in secondary school under The Secondary Educational Service Area Office 3 The results showed that 1. The factor of teachers’ work characteristics under The Secondary Educational Service Area Office 3 in overall at a high level. 2. The factor of teacher’s work experience under The Secondary Educational Service Area Office 3 in overall at a high level. 3. The factor of teachers’ commitment under The Secondary Educational Service Area Office 3 in overall at a high level. 4. The relationship between individual characteristics and organizational commitment of teachers. There is a negative relationship in the lower level. Work characteristics with organization commitment of teachers. And the experience in working with the organization commitment of teachers. There are positive correlation significantly in moderate at 0.01 level. 5. The factors experienced in working in the expectation that a response is received from the Agency (E3), the factors of experience in operations and corporate attitudes towards colleagues and organizations (E4), the experience of practitioners felt that the school is dependable (E2), the factors of work that it is importance (J3), work characteristic in the freedom to work (J1) and the experience factor in the sense that their operations are important (E1). In regards to three factors that predicted the teachers’ commitment, the stepwise multiple regression analysis on the variables, it showed that six variables could through predicted the teachers’ commitment towards secondary school (66.10) as listed in the following order. The regressions equation in raw score regarding the teachers’ commitment towards the school was shown as follows: Y= .739 + .118 (E3) + .262 (E4) + .192 (E2) + .089 (J3) + .099 (J1) + .074 (E1) Zy= .158(E3) + .319 (E4) + .256 (E2) + .102 (J3) + .110 (J1) + .094 (E1)